Central Corneal Thickness and Intraocular Pressure Changes After Phacoemulsification and Their Association with Cataract Density: Doi:10.36351/pjo.v41i4.2147 - Gull, Ambreen; Imran Janjua, Muhammad; Tehmina Imdad (Pakistan Journal of Ophthalmology, 2025)
Purpose: To assess the changes in central corneal thickness and intraocular pressure following phacoemulsification and find their association with cataract density. Study Design: Observational analytical study. Place and Duration of Study: Benazir Bhutto Hospital, Rawalpindi Medical University, from January 2024 to December 2024. Methods: The study was carried out on 80 eyes undergoing uneventful phacoemulsification. Preoperative and postoperative central corneal thickness(CCT) and intraocular pressure (IOP) were measured using ultrasound pachymetry and Goldmann applanation tonometry, respectively, at day 1, week 1, and week 4. Cataract density was graded using the Lens Opacification Classification System III.Visual acuity was recorded pre- and postoperatively using the decimal notation Snellen chart. Data was analyzed using paired t-tests, repeated measures ANOVA, and Spearman correlation. Results: The mean preoperative Best corrected visual acuity (BCVA) was 0.208 ± 0.17 (range: 0.01–0.50) using the Snellen decimal notation chart. At four weeks postoperatively, the mean BCVA significantly improved to 0.823 ± 0.16. Mean CCT increased from 524.15±40.54 µm preoperatively to 574.92±44.72 µm on day 1 postoperatively, reducing to 525.89±40.50 µm by week 4. IOP showed a transient rise from 15.59±2.19 mmHg to 17.99±2.17 mmHg at week 1, returning to baseline at week 4. A significant positive correlation was found between cataract density and both postoperative day 1 CCT (ρ=0.421) and IOP (ρ=0.430). Conclusion: Phacoemulsification results in reversible changes in CCT and IOP. Cataract density is moderately associated with early postoperative corneal edema and IOP elevation.